Nonlinear dynamics of the financial-growth nexus in African emerging economies: The case of a macroprudential policy regime - Lindokuhle Talent Zungu (Economies, 2022)
A panel data analysis of nonlinear financial growth dynamics in a macroprudential policy regime was conducted in a panel of 10 African emerging countries from 1983-2020, where it had been a non-prudential regime from 1983-1999 and a prudential regime from 2000-2020. The paper explored the validity of invented U-shape hypothesis in the prudential policy regime as well as the threshold level at which excessive finance boosts growth using the panel smooth transition regression (PSTR) model. The PSTR model was adopted due to its ability to address the problems of endogeneity and heterogeneity in a nonlinear framework. The results reveal evidence of a nonlinear effect between financial development and economic growth, where the minimum level of financial development is found to be 60.5% of GDP, above which financial development increases growth in African emerging countries. The findings confirmed a U-shaped relationship, contradicting the invented U-curve hypothesis. The focal policy recommendation is that the financial sector should be given adequate consideration and recognition by, for example, implementing appropriate financial reforms, developing a suitable investment portfolio, and keeping spending on technological investment in Africa's emerging countries below the threshold. Again, caution is needed when introducing macroprudential policies at a low level of the financial system.
Keywords: 330; economic growth; financial development; African emerging markets; macroprudential policy; PSTR